Socio-philosophical observations of managerial activity - Mirzoyan, Valeri (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
Management has always been in the center of attention of philosophers, since it is one of the forms of subject-object relationships, within which the goal-setting of the subject of management is realized through the executive activity of the object. The successful activity of any organization is based on a certain management philosophy, formulated in the mission and objectives of the organization, its dominant values, code of conduct, etc. Philosophical understanding requires one of the key points of management activity – managerial decision making. It is important to find out the mental and socio-psychological reasons for mistakes when making decisions. In particular, the manager should overcome a purely pragmatic approach to solving problems and develop the ability to grasp and compre-hend the managerial situation more globally.
Keywords: management; science of management; socio-philosophical observation; manager; leader; managerial error; simple solution; mutual trust